Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

dy/dx = k(L-y) where k and L are constants y(0)= 0

How does one find the integral for this and whats the reasoning please?

share|cite|improve this question
this looks like a differential equation to me – user31280 Oct 21 '12 at 11:04
This has been answered many times on this site already... – Hans Lundmark Oct 21 '12 at 11:08
$dy/dx=f(x)g(y)$ gives $dy/g(y) = f(x)dx$ if $g(y)\ne 0$. – Frenzy Li Oct 21 '12 at 11:13
See here, for a similar example: – Hans Lundmark Oct 21 '12 at 11:14

This is a differential equation $y' = kL - ky$ with homogeneous equation $y_h' = - ky_h$ and particular equation $y_p = c(x)y_h$ and $y = y_h + y_p$

$y_h$ is obviously $k_1e^{-kx}$, $k_1$ another constant, the problem lies in finding $y_p$.

$y_p = c(x)y_h = c_1(x)e^{-kx}$ and $y_p' = c_1'(x)e^{-kx} - kc_1(x)e^{-kx}$ which is of the form $y_p' = c_1'(x)e^{-kx} - ky_p$, same with the initial problem. We then have $c_1'(x)e^{-kx} = kL$ and $\displaystyle c_1(x) = \int_{0}^{x} \cfrac{kL}{e^{-kt}}dt = kL \int_{0}^{x} e^{kt}dt= kL\left(\cfrac{e^kx}k-1\right)$ and $y_p = L-kLe^{-kx}$.

Thus, $y=y_h+y_p=k_1e^{-kx}+ L-kLe^{-kx}$, with $y(0) = 0$ one find $k_1= kL-L$ and finally $y = L(1-e^{-kx})$

share|cite|improve this answer
Thank you, finally got it! – John Oct 23 '12 at 8:54

if you divide both by $(L-Y)$ and multiple by $dx$,you get $\int(dy/(L-Y))=kdx$

or -$ln(L-y)=k*x+c$, multiply it by $-1$, you get $ln(L-Y)=-k*x-c$; now exponential it and you will be fine

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.